Perancangan Laporan Keuangan UMKM Pada An-An Hair Salon Menggunakan Microsoft Excel - Suriani; Santi Widiawati; Aulia Fuadah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This project is entitled "designing MSME financial reports at An-An hair salon using Microsoft excel" written by Aulia fuadah under the guidance of Mrs. Santi Widiawati, S.Pd., M.Ak., PIA. This study aims to simplify the recording of salon financial reports using Microsoft excel, so that cash flow income statements and balance sheets can be managed more effectively. The results showed that the use of excel helped reduce errors, speed up recording and facilitate financial analysis. With a more structured report, it is hoped that An-An hair salon can make better business decisions and improve business sustainability.